Health Impact and Cost-Effectiveness of Sugar-Sweetened Beverage Taxes for Reducing Cancer Burden in the United States (P22-010-19). (13th June 2019) - Griecci, Christina; Du, Mengxi; Kim, David; Eom, Heesun; Ruan, Mengyuan; Cudhea, Frederick; Wong, John; Wilde, Parke; Rehm, Colin; Michaud, Dominique; Lee, Yujin; Micha, Renata; et al.
Abstract: Objectives: Sugar sweetened beverage (SSB) intake is pervasive in the U.S. and a critical risk factor for weight gain and obesity. Obesity is a preventable factor associated with 13 types of cancers. While SSB taxes can lower SSB intake, the potential impact on cancer outcomes, health costs, and cost-effectiveness in the U.S. is lacking. We aimed to evaluate the health outcomes, costs, and cost-effectiveness of a national SSB tax policy for reducing obesity-related cancer in the U.S. Methods: We used the Diet Cancer Outcome Model (DiCOM), a probabilistic cohort state-transition model, to project the effect of a national $0.01 per oz SSB excise tax on 13 obesity-associated cancers among U.S. adults age 20+ years over their lifetime. Model inputs included national demographic and dietary data from the National Health and Nutrition Examination Survey (NHANES) 2013–2016, policy effects, diet-BMI effects, and BMI-cancer effects from meta-analyses, and policy and cancer costs from established sources. Cost-effectiveness was evaluated as net costs with 3% annual discounting, under both government affordability and societal perspectives. Probabilistic sensitivity analyses jointly incorporated uncertainty in model inputs using 1000 simulations. Results: The SSB tax policy was estimated to prevent 20, 545 (95% uncertainty interval [UI]: 12, 586 to 32, 000) new cancers cases and 10, 181 (6362 to 16, 000) cancer deaths and add 67, 100 (41, 100 to 104, 505) quality-adjusted life years (QALYs) over lifetime. Largest health benefits were seen for endometrial, kidney, and liver cancer. The SSB tax was estimated to generate $1.17 billion industry compliance costs, $1.20 billion in government implementation costs, and $5.4 billion in lifetime medical savings for the 13 types of cancer. The SSB tax was net cost saving from a societal perspective and government affordability perspective, at $3.2 billion (95% UI: $2.4 to $4.1) and $4.1 billion (95% UI: $3.4 to $4.9), respectively, not including the $6.6 billion generated from tax revenues. Conclusions: Our modeling estimates that a national $0.01 per oz SSB tax would reduce obesity associated cancer cases and deaths among U.S. adults, and be cost savings from both a societal perspective and government affordability perspective. Funding Sources: NIH/NIMHD. Supporting Tables, Images and/or Graphs: